Reports of Conferences, Institutes, and Seminars. Issue 4 (2nd October 2019) - Bane, Treasa; Wong, Elise Y.; Stuart, Shelby; Heady, Megan; Lynn, Katie; Copeland, Jessie L.; Jones, Lynne; McAllister, Courtney; Rogers, Kristin; Patrick, Martin; Beh, Eugenia; Song, Xiaoyan; et al.
Abstract: This column covers several conference sessions from the 14th annual Electronic Resources & Libraries Conference, providing guidance on how to navigate ebook duplication, improving documentation and workflows, implementing OpenAthens, and experiences with Project SILLVR (Streaming Interlibrary Loan Video Resources)and knowledge bases and related tools (KBART) automation. There is also a report from IFLA's SIG Library Publishing Mid-Term meeting, which was an ideological meeting in nature, discussing community building, resource sharing, and status updates. A report from the 2018 Charleston Conference is also included.